2019
DOI: 10.3389/fmicb.2019.00365
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Bioluminescence: Light Emission in Photobacterium phosphoreum Is Not Under Quorum-Sensing Control

Abstract: Bacterial-bioluminescence regulation is often associated with quorum sensing. Indeed, many studies have been made on this subject and indicate that the expression of the light-emission-involved genes is density dependent. However, most of these studies have concerned two model species, Aliivibrio fischeri and Vibrio campbellii . Very few works have been done on bioluminescence regulation for the other bacterial genera. Yet, according to the large variety of habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 67 publications
(95 reference statements)
0
27
0
Order By: Relevance
“…Uropathogens are capable of producing toxins that can alter and affect normal bodily functions, and this toxin production is essential for their infectivity and pathogenicity. However, the production of bioluminescence in the genus Photobacteria is not associated with quorum sensing [23,40]. Further, data gathered on the effects of high concentrations of non-pathogenic E. coli cells on P. leiognathi signal intensity demonstrated that neither quorum sensing nor toxin production was responsible for the blackout phenomenon seen with uropathogens.…”
Section: Mechanism Of Action For Bioluminescence Inhibitionmentioning
confidence: 96%
See 1 more Smart Citation
“…Uropathogens are capable of producing toxins that can alter and affect normal bodily functions, and this toxin production is essential for their infectivity and pathogenicity. However, the production of bioluminescence in the genus Photobacteria is not associated with quorum sensing [23,40]. Further, data gathered on the effects of high concentrations of non-pathogenic E. coli cells on P. leiognathi signal intensity demonstrated that neither quorum sensing nor toxin production was responsible for the blackout phenomenon seen with uropathogens.…”
Section: Mechanism Of Action For Bioluminescence Inhibitionmentioning
confidence: 96%
“…Bioluminescent bacteria are prokaryotes that can produce their own light solely from their unique metabolic activity. Marine luminous bacteria have been studied and extensively utilized in the biotechnological detection of toxic chemicals, pollutants, pesticides, dissolved oxygen, freshness, quorum sensing, ATP, and other physicochemical conditions [17][18][19][20][21][22][23]. Bioluminescence is living light; the partial or complete inhibition depends on the cells' viability, which is affected by the cells' immediate physicochemical condition and/or direct exposure to toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…The fish-gut microbiota has been reported to be particularly of low cultivability, with less than 0.1 % of the total microbial community cultivable (Zhou et al, 2014), although the level of cultivability may be taxon dependent (Ward et al, 2009). Today, advanced molecular techniques offer a wide variety of culture-independent methods, such as next-generation sequencing (NGS), for analyzing fish microbiota (Tarnecki et al, 2017).…”
Section: Enteric Associations In Marine-fish Gutsmentioning
confidence: 99%
“…The bioluminescence mechanism of luminescent bacteria has been fully studied and characterized (Inouye, 1994 ; Moore and James, 1995 ; Bourgois et al, 2001 ; Vetrova et al, 2007 ; Nijvipakul et al, 2010 ; Bergner et al, 2015 ; Brodl et al, 2018 ; Tanet et al, 2019 ). Generally, luciferase, reduced flavin mononucleotide (FMNH 2 ), oxygen (O 2 ), and long-chain fatty aldehyde (RCHO) are prerequisite for the luminescence emitted by luminescent bacteria in which flavin mononucleotide (FMN) was reduced to FMNH 2 by the catalyzation of NAD(P)H: FMN oxidoreductase.…”
Section: Physiological Mechanism Of Bioluminescence From Luminescent mentioning
confidence: 99%